2009
DOI: 10.1159/000227279
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Genotype E of Hepatitis B Virus in an Indian Population

Abstract: Twenty-one hepatitis B virus (HBV) isolates from the state of Haryana (North India) were studied for genotype, subgenotype, serotype distribution and precore mutations. Assays of alanine aminotransminase (ALT) and HBeAg were performed on all samples. Genotypes, subgenotypes and serotypes were determined by amplification of pre-S1/S2 regions followed by RFLP and also by phylogenetic analysis of amplified products. Mutations were studied by amplification and sequencing of the precore region. Twenty-four percent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 23 publications
3
12
0
Order By: Relevance
“…of Sharma et al, 21 who observed genotype D and genotype A in North Indian patients, and in accordance with the study of Madan et al, 22 who observed genotype D and A but we did not observe genotype C as the study of Madan et al, 22 and in accordance with the study of Singh et al, 23 who observed genotype D and A in North Indian population. But, we did not observe genotype E in our population as the study of Singh et al, 23 in accordance with the study of Kar et al 24 Chattopadhyay et al 25 reported predominance of genotype D followed by genotype A among patients with chronic liver disease from New Delhi.…”
Section: Conflicts Of Interestsupporting
confidence: 92%
See 1 more Smart Citation
“…of Sharma et al, 21 who observed genotype D and genotype A in North Indian patients, and in accordance with the study of Madan et al, 22 who observed genotype D and A but we did not observe genotype C as the study of Madan et al, 22 and in accordance with the study of Singh et al, 23 who observed genotype D and A in North Indian population. But, we did not observe genotype E in our population as the study of Singh et al, 23 in accordance with the study of Kar et al 24 Chattopadhyay et al 25 reported predominance of genotype D followed by genotype A among patients with chronic liver disease from New Delhi.…”
Section: Conflicts Of Interestsupporting
confidence: 92%
“…But, we did not observe genotype E in our population as the study of Singh et al, 23 in accordance with the study of Kar et al 24 Chattopadhyay et al 25 reported predominance of genotype D followed by genotype A among patients with chronic liver disease from New Delhi.…”
Section: Conflicts Of Interestsupporting
confidence: 87%
“…HBV/D with subtypes D1–D5 is prevalent in the Mediterranean region expanding through South Asia up to India [8]. HBV/E is restricted to West Africa [11] but some studies reported the presence of this genotype in South America [12] and India [13]. This genotype is characterized by a low genetic diversity among strains from throughout the world [14].…”
Section: Resultsmentioning
confidence: 99%
“…Genotype E has been isolated from Pygmies [33] and the Khoi San [Kramvis, unpubl. data], and in Colombia [34] and India [35] in individuals with no history of travel to or from Africa. Without an accurate determination of the nucleotide substitution rate of HBV, the variance of the estimated age of genotype E will be difficult to resolve.…”
Section: Genotype Ementioning
confidence: 99%